Phytochemical study of selected species from (rubiaceae and guttiferae) families and biological study of isolated compounds as well as synthetic schiff bases compounds / Khaled Abdullah Ali Alkadi - Ali Alkadi, Khaled Abdullah (2019)
A series consisting of 30 novel imidazo [4,5-b]pyridine benzohydrazones derivatives have been synthesized and evaluated for antiglycation and antioxidative activities. Result obtained showed that di and tri-hydroxy substituted compounds showed good activity with compound 25 (140.16 ± 0.36 lM), which is twice lower than Rutin. The results also showed certain correlation between antiglycation and antioxidant activities. Dried leaves of Garcinia griffithii and stem bark of Garcinia malaccensis (Guttiferae) were extracted under reflux with MeOH and fractionated through vacuum liquid chromatography (VLC) technique using different polarity. Phytochemical investigations have revealed two known xanthones derivatives, 1,3,5,6-Tetrahydroxy-7-(3-methylbut-2enyl) xanthone (1) and Rubraxanthone (2) and four compounds 5-Hydroxyflavone (3), 2’-Hydroxyflavanone (4), Paeonol (5) and Bergenin (6). All spectroscopic data were showed excellent agreement with the previously published results. All those compounds were determined for their ability to inhibit platelet aggregation induced by arachidonic acid (AA), collagen and adenosine diphosphate (ADP). Were showed strong antiplatelet aggregation activities at 100 μg/ml in human whole blood in vitro. Both 1,3,5,6-Tetrahydroxy-7-(3-methylbut-2-enyl) xanthone, Rubraxanthone, 5-Hydroxyflavone, Paeonol (5) and Bergenin (6) showed marked inhibitory effect on platelet aggregation caused by the three inducers. 2’-Hydroxyflavanone (4) showed inhibitory effect on platelet aggregation caused by two inducers AA and ADP. The IC50 value of all the compounds shows inhibition higher than that of aspirin. The compounds isolated from Prismatomeris glabra were determined for cytotoxicity and antiinflammatory activities using THP-1 macrophage cell line. Cell viability was determined using the (MTS) assay. Cells were treated with amentoflavone, 5,7,4’-hydroxyflavonoid and stigmasterol, with various concentration (0- 30 μg/mL) on THP-1 cells for (24, 48 and 72 h) incubation , x̄ ± S.D. (n=3), and then incubated with MTS reagent for 2 h. shows the cell viability at (0-30 μg/mL) of compounds amentoflavone, 5,7,4’- hydroxyflavonoid and stigmasterol. After 24 h of incubation, IC50 values for amentoflavone was (21 μg/mL ≡ 38 M), 5,7,4’- hydroxyflavonoid was (18 μg/mL ≡ 66 M) and stigmasterol was (20 μg/mL ≡ 48.5 M). The effects of the compounds (5,7,4’-hydroxyflavonoid, amentoflavone and stigmasterol) on PGE2, TNF-α and IL-6 expression in human THP-1 derived macrophages cells were pretreated with different concentration (0-30 μg/mL) for 24h. Compounds significantly reduced the production of TNF-α, IL-6 and PGE2, in dose-dependent manner.